2021
DOI: 10.1016/j.tracli.2021.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Locally harvested Covid-19 convalescent plasma could probably help combat the geographically determined SARS-CoV-2 viral variants

Abstract: The only effective way to provide individuals with herd immunity against the novel coronavirus [SARS-CoV-2] is to administer an effective vaccine that will help check the current pandemic status. In India, the central drugs standard control organization (CDSCO) has granted the emergency-use authorization [EUA] to three vaccines namely, Covishield (live vaccine, Oxford AstraZeneca, United Kingdom being manufactured by the Serum Institute of India), Covaxin (inactivated vaccine, Bharat Biotech, India) and Sputni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Another argument for CCP is that it exhibits a more dynamic change than monoclonal antibodies as recovered donors are exposed to different variants. One study suggested that locally collected CCP may exhibit better activity against variants circulating in the region 12 . However, CCP units that were collected during infection waves linked to older variants may have decreased effectiveness so fresher units are preferred over older collections 13 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another argument for CCP is that it exhibits a more dynamic change than monoclonal antibodies as recovered donors are exposed to different variants. One study suggested that locally collected CCP may exhibit better activity against variants circulating in the region 12 . However, CCP units that were collected during infection waves linked to older variants may have decreased effectiveness so fresher units are preferred over older collections 13 .…”
Section: Discussionmentioning
confidence: 99%
“…One study suggested that locally collected CCP may exhibit better activity against variants circulating in the region. 12 However, CCP units that were collected during infection waves linked to older variants may have decreased effectiveness so fresher units are preferred over older collections. 13 Although all CCP units are collected and undergo antibody titer testing according to FDA guidelines, 5 there are differences in how various immunoassays correlate with neutralizing antibody levels, which are often used as a surrogate marker for effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…As such they serve as an ideal target for vaccine development aimed at minimizing the spread of the disease (8)(9)(10)(11). As a result, the antibody response to spike protein post-vaccination is critical for adjudging the 'effectiveness' of the vaccine (12). The detectable levels of IgM and IgG antibodies could provide information regarding seroconversion, as the detection of IgM antibodies indicates a recent exposure whereas the detection of IgG antibodies in the absence of detectable IgM antibodies indicates long-term immunity against the virus (13).…”
Section: Introductionmentioning
confidence: 99%